Light Polarization Using Ferrofluids and Magnetic Fields - Alberto Tufaile; Timm A. Vanderelli; Adriana Pedrosa Biscaia Tufaile (Advances in Condensed Matter Physics)
We are presenting an experimental setup based on polarized light, enabling the visualization of the magnetic field of magnetic assemblies using a Hele-Shaw cell filled with ferrofluids. We have simulated the observed patterns with hypergeometric polynomials.